eDNA assessment of scleractinian diversity and distribution in Lemukutan Island, Indonesia - IWAN KUNCORO; NEVIATY PUTRI ZAMANI; BEGINER SUBHAN; NI KADEK DITA CAHYANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kuncoro I, Zamani NP, Subhan B, Cahyani NKD. 2023. eDNA assessment of scleractinian diversity and distribution in Lemukutan Island, Indonesia. Biodiversitas 24: 4185-4191. Coral reefs are one of the most degraded and endangered tropical marine ecosystems. The study of biodiversity and its distribution is significant for biomonitoring. Lemukutan is an island that has a coral reef ecosystem with high biodiversity. This study aims to examine the biodiversity of coral species on Lemukutan Island using the Environmental DNA (eDNA) approach to survey scleractinian diversity across Lemukutan Island. Surface seawater samples were taken from five sites. eDNA sample extracted from the filter paper used for filtration Polymerase Chain Reaction (PCR) amplification was performed with Internal Transcribed Spacer (ITS2) primers, and Next Generation Sequencing was used to examine the results. The result found 2,413 Amplicon Sequence Variance (ASVs) and 275,000 reads from seawater samples from 5 sites. 87 ASVs from the eukaryotic group (146,378 reads) and 1,926 ASVs from unidentified taxa (128,622 reads) were identified. The highest phylum of eukaryotic taxa obtained was Phylum Cnidaria, with 332 ASVs (72% of the total eukaryotic ASVs) and 77,428 reads (85% of the total eukaryotic reads). There are 43 species of eukaryotes, including the Cnidaria group-based eDNA. The results show 14 species of scleractinian and different species compositions from each sampling location. In conclusion, the eDNA method has sensitive results in detecting 14 scleractinian species composition without destroying habitats and organisms. Knowledge regarding species diversity and distribution of taxa with eDNA assessment can be used as a reference in monitoring coral reef ecosystems on Lemukutan Island, Indonesia.